Recent applications of chiral calixarenes in asymmetric catalysis - Durmaz, Mustafa; Halay, Erkan; Bozkurt, Selahattin (Beilstein Journal of Organic Chemistry, 2018)
The use of calixarenes in asymmetric catalysis is receiving increasing attention due to their tunable three-dimensional molecular platforms along with their easy syntheses and versatile modification at the upper and lower rims. This review summarizes the recent progress of synthesis and use of chiral calixarenes in asymmetric syntheses which emerged later than 2010.
Keywords: asymmetric catalysis; chiral calixarene; organocatalyst; supramolecular catalyst